Transforming Pesantren: Adaptive Strategies in the Context of Educational Decentralization in Indonesia - Hasyim, Abd. Wahid; Chair, Abd. (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
The decentralization of governmental administration during Indonesia's Reform Order era has facilitated educational autonomy, enabling Islamic boarding schools (pesantren) to redefine their institutional frameworks. This study examines the transformation of pesantren in South Tangerang City within the context of educational autonomy. Using a qualitative methodology that combines historical and phenomenological approaches, data were gathered through in-depth interviews, observations, literature reviews, and focus group discussions. The research identified seventy pesantren distributed across seven sub-districts, with a significant concentration in Ciputat. These pesantren have undergone substantial transformations, integrating traditional religious education, such as kitab studies, with modern schooling systems, including madrasas and formal educational institutions. Certain pesantren serve specific demographics, such as orphans and converts, while others focus on formal education or the practice of specific Islamic tariqah. The observed transformations encompass human resources, curricula, educational facilities, and management structures. These changes highlight pesantren's dual commitment to preserving their religious heritage while responding to contemporary societal needs, embodying the philosophy of holistic education (tafaqquh fi ilmi al-ukhrawy wa al-dunyawy). This study contributes to the discourse on educational autonomy by offering a comprehensive perspective on pesantren's evolving role in balancing tradition and modernity within a dynamic educational landscape.